New Simple Synthesis of Quinoline-4-carbonitriles - Bujok, Robert; Trawczyński, Adam; Wróbel, Zbigniew; Wojciechowski, Krzysztof (Synlett, 2012)
Alkylation of 2-nitrobenzyl cyanides with α-halomethyl ketones furnishes ketonitriles which upon reduction with tin(II) chloride form quinoline-4-carbonitriles in good yields.
Keywords: quinolines; reduction; nitriles; alkylation; ketones; tin